The Effect Of Webtoon Application Towards Students Reading Comprehension In Narrative Text - Fajriyah, Enur; Sudirman, Ade; Riandi (CV. Kurnia Grup, 2025)
This research paper aim to investigation the effect of webtoon application towards students’ Reading Comprehension in narrative text. The research paper used the quantitative research design with the characteristics of experimental method that is design into two classes. They are experimental and control class. The population of this research is class XI of SMKN 1 Malingping, they consists 327 students. The sample of this research is XI MPLB1as an experimental class consists 30 students and XI MPLB2 as a control class consists of 30 students. The total of sample is 60 students. The instrument is a test and data of this research are collected by giving pre-test and post-test. The data is analyzed using SPSS version 30.0 program including mean, standard deviation and t-test. It could be seen from the result of the post-test of experimental and control class. The findings reveal that the data analysis and interpretation of the research, it is clear there is a significant effect of webtoon application towards students’ reading comprehension in narrative text. It can be seen, the minimum score pre-test experimental calss is 40, maximum is 75, mean 61,17 andstandard deviation 8,972. While the minimum score post-test experimental class is 60, maximum 90, mean 76,17 and standard deviation 7,844. Furthermore, the minimum score of control class is 40, maximum 75, mean 60,67 and standard deviation 8,066. While the minimum score post-test of control class is 60, maximum 85, mean 71,67 and standard deviation 5,921. The result of t-test obtained sig. value 0.007 ≤ ??? = 0.05. Ha is accepted and Ho is rejected. It can conclude that there is a significant effect of Webtoon application towards students reading comprehension in narrative text.